2011
DOI: 10.1111/j.1365-2621.2011.02883.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drying methods on volatile compounds, fatty acids and antioxidant property of Thai kaffir lime (Citrus hystrix D.C.)

Abstract: This study investigated the changes in colour, volatile compounds, fatty acids, total phenolic content (TPC), total flavonoid content (TFC) and antioxidant activity of kaffir lime leaves (makrud in Thai) Citrus hystrix D.C. after three drying treatments, namely hot-air (HA) drying, low relative humidity (LRH) air drying and far-infrared radiation (FIR) drying. Overall, when compared with fresh leaves, a slight decrease in L* values of the three dried samples was observed. TPC, TFC and ferric-reducing ⁄ antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 60 publications
(75 reference statements)
1
26
1
Order By: Relevance
“…Recently, the effect of drying methods on seventeen volatile compounds obtained from headspace method was investigated by Raksakantong et al . (). However, the effects on volatile compounds in food matrix phase and key odourants of kaffir lime leaf have not been reported.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, the effect of drying methods on seventeen volatile compounds obtained from headspace method was investigated by Raksakantong et al . (). However, the effects on volatile compounds in food matrix phase and key odourants of kaffir lime leaf have not been reported.…”
Section: Introductionmentioning
confidence: 97%
“…However, it can give rise to other alterations that affect the quality of the final product, such as changes in their appearance and odour. Raksakantong et al (2012) found that drying methods affected some properties of kaffir lime leaf, including colour, fatty acid composition, antioxidant property and content of some volatile compounds. However, drying method is not the only crucial factor affecting quality of kaffir lime leaf, drying temperature can also cause certain changes to the herb.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic volatile compounds such as eucalyptol, linalool, eugenol and methyl eugenol in samples dried by microwave were higher than in samples dried by traditional methods. Raksakantong et al (2012) investigated the changes in volatile compounds of kaffir lime leaves using three drying treatments, namely hot-air drying, low relative humidity air drying and far-infrared radiation drying. Drying increased the concentrations of volatile components, such as citronellal with up to 83% using low relative humidity air drying, compared with the results for fresh leaves (56%).…”
Section: Introductionmentioning
confidence: 99%
“…; Raksakantong et al . ). Thus, the effect of different drying methods on the flavor of fish deserves to be investigated.…”
Section: Introductionmentioning
confidence: 97%